POLITICAL ACTIVISTS OF STUDENTS OF THE FACULTY OF USHULUDDIN AND ISLAMIC STUDIES, STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA IN A CASE STUDY DEMONSTRATION: AT THE MEDAN CITY DPRD BUILDING - Juni Yanti Siagian; Abu Sahrin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to explain why students of the world Faculty of Ushuluddin and Islamic Studies, North Sumatra State Islamic University, regard demonstrations as their primary form of political activism, analyze the decision-making process preceding collective action, and describe the practical manifestations of political activism during demonstrations at the Medan City Regional House of Representatives (DPRD). A qualitative approach employing a case study design was adopted to gain an in-depth understanding of student political activism. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that demonstrations are perceived as the most effective political channel for expressing public aspirations, scrutinizing government policies, and exercising social oversight. Interview evidence indicates that participation in demonstrations is preceded by systematic issue assessment, organizational discussion, collective deliberation, and internal consolidation rather than emotional impulses or spontaneous reactions. Furthermore, student political activism extends beyond street demonstrations to include academic policy analysis, evidence-based advocacy, political education, organizational networking, and the formulation of public-oriented demands. These findings suggest that demonstrations represent a substantial expression of participatory democracy and reinforce students' roles as agents of change, social controllers, and moral forces in promoting accountable governance, responsive public policies, and a more democratic civic culture.